"This is where I belong:" a narrative study of professional commitment to a new criminal justice agency - Arriagada, Isabel (Crime, law and social change, 2023)
Scholars of penal change have established a rich theoretical understanding of the macro- and meso- level processes that explain the emergence, diffusion, and success of penal developments. Similarly enthusiastic examinations of the agentic aspects of professional commitment to criminal justice institutions are necessary to better understand the relationship between micro-level individual processes and the endurance and success of penal projects. The present study builds on existing analyses of cause lawyering and indigent criminal defense to examine the personal narratives of penitentiary defenders, lawyers working for the Unit of Penitentiary Defense, a novel Chilean public agency that offers legal assistance and enables convicted prisoners to file grievances and report rights violations before criminal courts. By drawing on 45 in-depth semi-structured interviews, I analyze the ways in which these attorneys incorporate biographical experiences and life events into coherent stories that both support and construct their professional identity as legal aid lawyers despite adverse working conditions. Four narratives are prevalent in their accounts: identification, privilege, calling, and admiration. These narratives demonstrate that criminal justice professionals engage in meaning-making processes through the creation of biographical accounts that tie personal and professional self-understandings together. The contribution of the article is thus twofold: it situates the role of individual agency in the development of penal projects and provides a novel explanation as to how legal aid lawyers become personally and professionally invested in indigent defense.